Lankesterella and Isospora Coccidians: Differences in Host Specificity of Blood Parasites in Passerines - Saravana Bhavan Venkatachalam, Ashwin Kumar; Brzoňová, Jana; Svobodová, Milena (Microorganisms, 2025)
Parasitic protozoa such as Lankesterella and Isospora are common in avian hosts, particularly in passerines. Despite their high prevalence, the diversity of these parasites within avian populations remains poorly understood. This study aimed to assess the diversity of Lankesterella and Isospora in passerine birds, using the SSU rRNA gene to characterize and compare the genetic variation in both parasites across multiple avian host species. For Isospora, the extraintestinal blood stages and oocysts from feces were compared. Minimum spanning networks were constructed to visualize haplogroups in relation to host specificity and to reveal the identity of various developmental stages. A total of 122 sequences from eight passerine species were used to generate a haplotype network for Lankesterella, and a total of 103 sequences (64 from blood and 39 from feces) was used for Isospora. We detected a total of 36 haplotypes for Lankesterella and 33 haplotypes for Isospora. In Lankesterella, we confirmed that the sedge warbler has its own specific lineages, whereas other warbler species share lineages belonging to three haplogroups; blue, great, marsh and willow tits have their own unique groups of lineages. Isospora is less host-specific than Lankesterella in avian hosts; nevertheless, Isospora sequences from blood and feces were identical in their respective hosts. Our findings provide insights into the diversity and host specificity of blood coccidians; moreover, we molecularly characterized the developmental stages of Isospora.
Keywords: host specificity; avian blood parasites; host–parasite interactions; Atoxoplasma; passerines; coccidia; Eimeriidae